Comparison of the efficacy and safety of standard‐ and high‐dose daptomycin: A systematic review and meta‐analysis. Issue 4 (13th February 2023) - Samura, Masaru; Takada, Keisuke; Hirose, Naoki; Kurata, Takenori; Nagumo, Fumio; Uchida, Masaki; Inoue, Junki; Tanikawa, Koji; Enoki, Yuki; Taguchi, Kazuaki; Matsumoto, Kazuaki; Ueda, Takashi; et al.
Abstract : Aims: Standard doses of daptomycin at 4 and 6 mg/kg were used for the treatment of skin and soft tissue for infections and bacteraemia, respectively. However, increased doses of daptomycin are recommended for complicated infections by Gram‐positive organisms. Methods: A systematic review was conducted using 4 databases. We compared treatment success between standard‐dose (SD, 4–6 mg/kg) and high‐dose (HD, >6 mg/kg) daptomycin in patients with all‐cause bacteraemia, complicated bacteraemia, infective endocarditis, osteomyelitis and foreign body/prosthetic infection as the primary outcome. We also compared the success between SD and HD2 (≥8 mg/kg) daptomycin treatments in patients with these diseases as the secondary outcome. The incidence of creatine phosphokinase (CPK) elevation was evaluated as safety. Results: In patients with complicated bacteraemia and infective endocarditis, the treatment success was significantly lower in the SD group than in the HD group (odds ratio [OR] 0.48, 95% confidence interval [CI] 0.30–0.76 and OR 0.50, 95% CI 0.30–0.82) and HD2 group (OR 0.38, 95% CI 0.21–0.69 and OR 0.30, 95% CI 0.15–0.60), respectively. A significant difference was demonstrated only in the HD2 group in patients with bacteraemia, including simple infection. SD did not decrease the success rate for the treatment of osteomyelitis and foreign body/prosthetic infection. The incidence of elevated CPK was significantly lower in SD group than in HD group. Conclusion: SD daptomycin was associated with significantly lower treatment success than HD in patients with complicated bacteraemia/infective endocarditis. The CPK elevation should be considered in patients treated with high daptomycin doses.